Metabolite fingerprint of "capim dourado" (Syngonanthus nitens), a basis of Brazilian handcrafts - Pacifico, Mariana [UNESP]; Napolitano, Assunta; Masullo, Milena; Hilario, Felipe; Vilegas, Wagner [UNESP]; Piacente, Sonia; Santos, Lourdes Campaner dos [UNESP] (Elsevier B.V., 2011)
Syngonanthus nitens is a grass-like species, whose flower stems assume a beautiful golden colour when dried, hence their common name "capim dourado". This plant represents an important source of income for rural communities, especially in Jalapao region, being the scapes used in the craft industry to make, together with buriti palm strips, traditional handcrafts from their coils. Therefore, considering that scapes and not flowerheads are used, we carried out an analytical study to define the metabolite fingerprint of both S. nitens parts, with the aim, on one hand, to identify the molecules responsible for the characteristic golden colour of the capim dourado herb and, on the other hand, to identify the occurrence of interesting constituents in S. nitens flowerheads to increase the value of this part of the plant, considered a waste matter of golden grass handcrafts. Therefore an HPLC-ESI-MS(n) method, based on high-performance liquid chromatography coupled to electrospray negative ionization multistage ion trap mass spectrometry, was developed to rapidly identify and guide the isolation of the secondary metabolites occurring in flowers and scapes. on the basis of the on-line HPLC-ESI-MS(n) screening, 17 compounds, including 6 new molecules, were isolated, and their structures were unambiguously elucidated by NMR spectroscopic data. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Syngonanthus nitens; C-Glycoside-flavones; Xanthones; HPLC-ESI-MS(n); NMR